Comparative Effectiveness of Cognitive Behavioral Therapy 5 Sessions and 12 Sessions Toward to Post Traumatic Stress Disorder on Post Flood Disaster Adolescent - Uray Fretty Hayati; Sari Fatimah; Ai Mardhiyah (JKP (Jurnal Keperawatan Padjajaran), 2018)
Abstract